Relational and technological assessment of CRM providers: A multifactor study - CLAYBAUGH, Craig C. (Institutional Knowledge at Singapore Management University, 2023)
The study examines how customers of relationship software provider perceive the technology they use and assess the relational elements of the exchange relationship. This study proposes and empirically tests a model integrating two technology components (positive prior experience and quality of technology) and four relational constructs (reputation, trust, risk, and overall relational satisfaction), and how these factors influence loyalty to a customer relationship management system provider. The findings suggest that both technology and relational factors influence loyalty. This paper provides a framework that highlights the technology and relational factors influencing loyalty to the CRM software provider, which is key to continuance.